Eksekusi Putusan Pailit Atas Perusahaan Modal Asing Di Indonesia - Muhammad Rendy Rifki Putra (Istinbath : Jurnal Hukum, 2021)
A bankruptcy Decision is a decision which states that a company is normatively bankrupt. Decisions were issued by the Indonesian Commercial Court and given to foreign companies in Indonesia due to the end of PKPU. This research is normative legal research, with a legal approach. The data sources are primary and secondary legal materials, which will be analyzed qualitatively. From this research, it is known that normatively a foreign capital company in Indonesia can be declared bankrupt by the Commercial Court if it fulfills the elements in Article 2 Paragraph (1) and Article 3 Paragraph (4) of the Bankruptcy Law. The problem that arises then is the execution stage of the decision. During the management and settlement of bankrupt assets, it is certain that other legal problems will arise, namely if the assets of the bankrupt debtor in Indonesia are not sufficient so that the debtor's assets are outside the jurisdiction of Indonesia. To overcome this problem, the government needs to enter into international agreements bilaterally and multilaterally, and the government also needs to ratify the Uncitral Model Law on Cross-Border with Guide to Enactment agreement made by the United Nations which can apply to fellow countries that ratify the regulation.